2020
DOI: 10.1089/scd.2019.0150
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocytes Derived from Patient-Specific Induced Pluripotent Stem Cells Recapitulate the Genetic Signature of Psoriasis Disease

Abstract: Psoriasis is characterized by hyperproliferation and defective differentiation of keratinocytes (KCs). Patients with psoriasis are at a high risk of developing diabetes and cardiovascular diseases. The debate on the genetic origin of psoriasis pathogenesis remains unresolved due to lack of suitable in vitro human models mimicking the disease phenotypes. In this study, we provide the first human induced pluripotent stem cell (iPSC) model for psoriasis carrying the genetic signature of the patients. iPSCs were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 78 publications
0
42
0
Order By: Relevance
“…Recently, we reported the generation of an iPSC line from a patient with a heterozygous deletion in FOXA2 gene (QBRIi009-A; FOXA2 +/− iPSC-C1) 24 and from a healthy control (QBRIi001; Ctr1-iPSCs) 25 . In this study, we generated additional iPSC lines from another healthy control (Ctr2-iPSCs).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we reported the generation of an iPSC line from a patient with a heterozygous deletion in FOXA2 gene (QBRIi009-A; FOXA2 +/− iPSC-C1) 24 and from a healthy control (QBRIi001; Ctr1-iPSCs) 25 . In this study, we generated additional iPSC lines from another healthy control (Ctr2-iPSCs).…”
Section: Resultsmentioning
confidence: 99%
“…Immunostaining and flow cytometry were performed as previously reported 27 , 29 . RT-PCR and qPCR were performed as previously reported 25 . (The antibody and primer details are listed in protocol was used in Supplementary Tables S2 and S3 .)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2012, Tsoi et al demonstrated a list of notable genes from the newly identified psoriasis loci and one of them was KLF4 (9p.31.2) [13]. Recently, in 2020, an upregulation of the KLF4 gene in psoriatic keratinocytes has been proved [14]. Therefore the studies cited encourage to deepen research on KLF4 in psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…Real time RT-PCR analysis was performed using GoTaq qPCR Master Mix (Promega) as previously described [20]. The primer details are listed in Table S2.…”
Section: Real Time Pcr Analysismentioning
confidence: 99%